استخدام " ChatGPT " و " Google Gemini " في تعلم العربي ة: تجربة طلبة السنة الأخيرة تخصص اللغة العربي ة م ع الاتصالا ت جامعة العلوم الإسلامية الماليزية - Muhammad Marwan Ismail; Siti Natrah binti Marzouki; Farah Nadia Harun; Wan Moharani Mohammad (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia